Answer:
The simplified answer of the given expression is 1.
Explanation:
When you see (f + g)(x), then it means that you are going to add f(x) and g(x) together. So, we are going to add the terms together that are given in the problem. We are also given the value of x which is 1. So, we are going to combine this information together so we can simplify the expression.
(f + g)(1)
f(x) = x - 1
g(x) = x²
(f + g)(1) = (1 - 1) + (1²)
Simplify the terms in the parentheses.
(f + g)(1) = 0 + 1
Add 0 and 1.
(f + g)(1) = 1
So, (f + g)(1) will have a simplified answer of 1.